Static, dynamic and fatigue analysis of a semi-automaticgun locking block - EKİCİ, BÜLENT; KURT, MUSTAFA; KAYNAK, YUSUF (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Reduction of the recoil forces on shotgun parts and even effects on the human body are a considerable importance during design of the semi-automatic shotgun parts. These forces are strongly affected by the dynamics of motion of rifle parts upon firing. Therefore, managing of these recoil forces would be crucial issue to produce functional, ergonomic, safe, reliable, and robust designs. in the literature, many researchers have investigated static, dynamic, and fatigue behaviors of most mechanical parts which especially take a role under the dynamic loads. However, shotgun parts have not been investigated formally yet. Therefore, in this study we particularly focused on investigating static, dynamic, and fatigue behaviors of a semi-automatic shotgun's locking block, which is an integral part of the shotgun mechanism during firing. In this study, techniques such as hardness measurements, analysis of the recoil forces of a semi-automatic shotgun, and finite element analysis were performed. Pro/Engineer Wildfire 3.0 series software was used to model the locking block and the other parts of the gun. Moreover, the finite element code ANSYS/LS-DYNA, and ANSYS Workbench were used to determine the stress distribution, and fatigue behaviors of the locking block, based on the Morrow Theorem. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Semi-automatic shotgun; Dynamic analysis; Fatigue analysis; Locking block; FEA; AISI-4340 STEEL